Empirical investigation of antecedents of perceived recovery service quality: evidence from retail banking in United Arab Emirates. (23rd September 2019) - Jham, Vimi
The banking sector has undergone tremendous change in all forms of service it provides to its customers. The aims of the banks are to avoid customer defection and lead to customer satisfaction. The purpose of the study was to examine the linkages among the constructs, such as customer perceived service quality, perceived service recovery quality and customer satisfaction in the banking industry. The moderating effect of negative brand perception due to service failure on recovery satisfaction was investigated. Random sampling methods are used to draw the sample from the population. Data was collected from 262 banking customers and were analysed with the help of structural equation modelling approach using smart PLS to understand the relationship among variables being studied. The results of the study contribute to the research by proving that customer service recovery satisfaction is dependent on customer perceived service quality and the moderating effect of negative brand perception due to service failure was insignificant.